(untitled) (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. ‘E la mirabile coppia apparve’: prolegomeni allo studio dei rapporti tra gaming and religion ˗ 2. Una mappatura del campo di indagine dei Digital Religion Studies: gaming as religion, didactic digital games … ˗ 3. … religion in gaming: ovvero cattedrali, moschee, schiere di angeli e demoni nelle narrazioni videoludiche ˗ 4. ‘Gli amori difficili’: la problematica relazione tra gaming and religion ˗ 5. Il diritto sulla scena: gaming and religion con gli ‘occhiali del giurista’ ˗ 6. Un puzzle di norme diverse e contrastanti: una radiografia sulla libertà di panorama in Europa … ˗ 7. … e in Italia ˗ 8. Postille conclusive: spunti di riflessione de iure condendo. Religious symbols and cultural heritage in videogames: intersections between gaming and religion, or two inescapably communicating destinies. New spaces for research and theoretical reflection ABSTRACT: Within a multiple reading grid, this contribution aims first of all to focus on the theme of the migration of religious symbols outside their natural ecosystem, electing videogames among the many ‘profane’ and even ’pop’ languages ​​of mass media society. Starting from the ancient marriage between games and religion, we will investigate the forms in which the religious material ˗ Christian and non ˗ is shaped within the world of videogames, trying to perimeter the field of investigation of that very particular line of research called Digital Religion Studies. Subsequently, starting from the famous case of Manchester cathedral, we will try to demonstrate the problematic nature of the relationship between gaming and religion. By shifting the wide angle to the field of law, the legal regime reserved for videogames will be elucidated, albeit skeletally, and then highlight how the classification systems of videogame contents do not protect the religious feeling of the faithful. The Manchester controversy will also provide an opportunity to investigate that labyrinthine plexus of provisions that governs the digital reproducibility of cultural heritage. It will end with some de jure condendo reflections on the regulation of religious data in videogames and on the subject of freedom of the panorama.